ANALYSIS OF LABORATORY TESTS FOR SEVERAL VIRAL SWINE DISEASES IN RUSSIA IN 2011–2017 - A. A. Shevtsov; O. N. Petrova; S. G. Remyga; A. S. Pershin; K. N. Gruzdev; A. S. Igolkin (Ветеринария сегодня)
Retrospective analysis of laboratory diagnostics carried out in Russia for dangerous viral swine diseases demonstrated that during the last seven years (the period when the Rosselkhoznadzor orders to implement National Monitoring Plans were executed) the amount of performed tests had increased. But it is not always possible to read the test results unambiguously and that requires the improvement of diagnostic practices supported by established rules of sampling, laboratory tests and obtained result submission. It means random tests shall be representative for tested populations, correlate with the prevalence of concerned infection and meet the required certainty. It  is also needed to establish the techniques of primary and confirmation tests, regulate the use of test kits (validated) preferring the use of the most effective and cheapest. Appropriately planned and implemented surveillance activities (including national monitoring) will contribute to minimization of financial expenses and improve their effectiveness at the same time.